Analisa Pengaruh Lebar Badan Jalan Dan Pengaruh Penempatan Traffic Light Terhadap Kemacetan Di Kota Bengkulu - Edito Dwi Antoro (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2019)
Congestion in the city of Bengkulu is often found on busy jams every day, namely jam jam compilation where the number of vehicles going in certain directions will be more. traffic is crowded with students, workers and employees who go to schools, campuses, workplaces and government offices so that they often do not relate to traffic regulations at crossroads, especially in the city of Bengkulu where traffic jams often occur, one of which is diverted by Four. The research methodology used is: Traffic Volume Analysis, Traffic Time Analysis, Service Level Analysis (LOS) = Service Level by collecting: the volume of traffic data or vehicles passing is done by distributing all the vehicles that were moved during the observation time. Recording is done every 15 minutes interval every hour of observation carried out on Monday, Wednesday, and starts from 07.00-09.00 (morning), 12.00-14.00 (noon), 16.00-18.00 (afternoon) From the results of the analysis carried out on traffic Traffic volume at Kompi intersection will be high when the entry and exit of school children and employees who will leave for office, namely at 07.00-09.00 with a volume of vehicles 3338 vehicles / hour or 2056 pcu / hour, then at 12.00-14.00 with a volume of 2677 vehicles / hour or 1684.3 pcu / hour, and at 16.00-18.00 with a volume of 2892 vehicles / hour or 1793.6 pcu / hour. For 6 hours the total vehicle research passing at Kompi intersection was 8907 vehicles / hour or 5533.9 pcu / hour. The highest volume and highest average speed occurs at 12.00-14.00 with a volume of 1684.3 pcu / hour and a speed of 17.67 km / hour. The performance of the Kompi Simpang service level at 07.00-14.00 depends on the service level C with a V / C 0 value, 5-0.41 while at 16.00-18.00 with a V / C value ratio of 0.43 indicates that traffic at the intersection of the company still depends on the level of satisfactory speed.